Comparing the Effect of Peer Support and Training by Healthcare Providers on Women's Breastfeeding Self-Efficacy - Asieh Moudi; Mahin Tafazoli; Hasan Boskabadi; Saeed Ebrahimzadeh; Hamid Salehiniya (Mashhad University of Medical Sciences, 2016)
Background & aim: Breastfeeding self-efficacy is an important factor affecting the success and duration of breastfeeding. Self-efficacy of people is influenced by four sources including performance accomplishments, vicarious experiences, verbal persuasion and the physiological responses which seem to be modified by breastfeeding intervention.  This study was conducted to compare the effect of providing peer support versus training women by health care providers on breastfeeding self-efficacy. Methods:This controlled clinical trial was conducted on 93 primiparous women in Mashhad health-care centres. Three centres were selected as clusters and subjects who attended each cluster were randomly allocated to three groups of peer support, training by health care providers and control. The peer support group received support from their peers four times. Subjects who were trained by health care providers participated in four training sessions by health care providers and the control group only received the routine care. At the end of the eighth postpartum week, data were collected using the breastfeeding self-efficacy scale. The data were analysed using ANOVA and paired t-test with SPSS, version 14. Results: The mean score of self-efficacy at the end of the eighth postpartum week, in the peer support, training by healthcare providers and control groups, were 54.4±9.75, 50.8±13.05 and 56.4±9.49, respectively. The three groups showed no significant differences in terms of breastfeeding self-efficacy score at the end of the eighth postpartum week (P-value=0.125). Breastfeeding self-efficacy score at baseline and at the end of the eighth postpartum week were significantly different in peer support and training by health care providers groups (P=0.05). Conclusion: Peer support and training by healthcare providers have similar impact on breastfeeding self-efficacy in primiparous women. So they could be used interchangeably to promote breastfeeding behavior.